Rationale, development and implementation of the ReACanROC registry for out-of-hospital cardiac arrests in France and Canada. Issue 7 (2nd June 2021) - Heidet, Matthieu; Hubert, Hervé; Grunau, Brian E; Cheskes, Sheldon; Baert, Valentine; Fraticelli, Laurie; Freyssenge, Julie; Lecarpentier, Eric; Stitt, Audra; Tallon, John M; Tazarourte, Karim; Truong, Courtney; et al.
Abstract : France and Canada prehospital systems and care delivery in out-of-hospital cardiac arrests (OHCAs) show substantial differences. This article aims to describe the rationale, design, implementation and expected research implications of the international, population-based, France-Canada registry for OHCAs, namely ReACanROC, which is built from the merging of two nation-wide, population-based, Utstein-style prospectively implemented registries for OHCAs attended to by emergency medical services. Under the supervision of an international steering committee and research network, the ReACanROC dataset will be used to run in-depth analyses on the differences in organisational, practical and geographic predictors of survival after OHCA between France and Canada. ReACanROC is the first Europe-North America registry ever created to meet this goal. To date, it covers close to 80 million people over the two countries, and includes approximately 200 000 cases over a 10-year period.